Effectiveness of Comprehensive Therapy vs. Standard Treatment in Diabetic Foot Ulcer Healing: A Retrospective Cohort Study - Ana Patricia Bautista; Inoue Mei Haruka; Nguyen Thi Mai; Kim Hoa Ngan; Chole Scarlet Charlotte (Journal of Wound Research and Technology, 2025)
Background: The Diabetic foot ulcer (DFU) is the tip of a very significant complication of diabetes mellitus (DM), often leading to grave outcomes in infection and eventually amputation with increased mortality. Many factors mess up the healing of DFUs: neuropathy, peripheral arterial disease, and hyperglycemia, just to mention a few. The best published healing outcomes have been reported with an integrated therapy consisting of Health care, intensive glucose management, wound care, and psychosocial support, although standard treatments provide only wound care and blood glucose management. Purpose: This study will check how effective complete therapy is in improving DFU faster than normal treatment. It will also examine how blood sugar control, insulin help, and mental support affect wound healing. Methods: A Cohort of 360 DFU patients from Seamen’s Hospital Manila was analyzed. Patients were divided into two groups: 180 received standard treatment and 180 received comprehensive therapy. Comprehensive therapy included intensive glucose control plus advanced wound care and psychosocial support. Healing success is defined as complete wound closure within 12 weeks. Statistical analyses, including chi-square tests, t-tests, and Cox proportional hazards regression, were performed to evaluate the impact of different factors on wound healing. Results: The comprehensive therapy group did markedly better, with an 85% healing success rate and average healing time of 8.3 weeks, compared to 55% and 11.7 weeks in the standard treatment group (p < 0.001). Multivariate analysis showed that glycemic control (HbA1c < 7%) turned out to be a significant predictor of faster healing as well as insulin therapy (HR =1.60 and HR =1.38, respectively). Psychosocial support also contributed positively to healing outcomes. Conclusion: Total treatment, covering wound care, blood sugar control, and mental social help, greatly speeds up DFU healing and cuts down the time taken to heal. This way should be called the best method for handling DFU and improving patient results.